Changes Related to the First Aid in Water Lifesaving in Poland (1962-2020) - Iwona Tabaczek-Bejster; Jerzy Kiszka; Grzegorz Konieczny (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
In 1962, Water Volunteer Rescue Service (WOPR) was established. From the beginning of its activity, this organization has established cooperation with the Polish Society of Anaesthesiology. In 1997, the regulation of the Council of Ministers was published in the Journal of Laws of the Republic of Poland, defining the safety conditions for people who are swimming, bathing and practicing water sports. WOPR was authorized to perform tasks related to the safety of persons staying at the body of water. In 2007, a breakthrough in the development of the first aid in water rescue took place in Poland. On January 1, 2007, the Law on State Emergency Medical Services entered into force. On its basis, the system of State Emergency Medical Services was created. WOPR has become one of the units cooperating with this system. On January 1, 2012, the new act on the safety of people staying in water areas was introduced. On its basis, radical changes in lifesaving have been made. The study analyzed the evolution of the first aid rules for lifesavers in Poland. It presents changes in ways of conduct in artificial lung ventilation and chest compressions in drowning people.